Identification of genes resistant to biotic factors in the winter wheat samples - N. N. Vozhzhova; D. M. Marchenko; E. V. Ionova (Зерновое хозяйство России)
The article presents the study results of 1708 collection and breeding samples of winter soft and durum wheat developed by the department of wheat breeding in the FSBSI “Agricultural Research Center “Donskoy”. The samples were studied on the presence of brown rust resistant genes (Lr9, Lr10, Lr19, Lr24, Lr26, Lr34, Lr37), stem rust (Sr32, Sr44), yellow rust (Yr5, Yr24) and leaf blotch (Stb2, Stb4). The estimation of the samples was conducted by the PCR. The resistant genes were identified in 70% of the studied samples. The screening identified 132 samples which carry 3 and more genes resistant to biotic factors in different variants. The samples which possess genes resistant to biotic factors are recommended to use as donors in the breeding programs.